Economic and economic-statistical designs of the T2 control charts with SVSSI sampling scheme. Issue 20 (18th October 2017) - Katebi, Mehdi; Seif, Asghar; Faraz, Alireza
ABSTRACT: Recent studies have shown that the adaptive T 2 chart with two different sampling interval and three sample sizes (SVSSI) shows a good performance in detecting small to large shifts in the process mean. This paper investigates the economic and economic statistical designs of the SVSSI T 2 charts. We use the Markov chain approach to developing the cost model proposed by Costa and Rahim (Journal of applied statistics 2001; 28: 875–885). A genetic algorithm approach is used to find the optimal solutions. Using numerical examples, we illustrate the performance of the proposed model and compare the statistical, economic, and economic statistical designs of the SVSSI T 2 chart with respect to the economic and statistical criteria. Furthermore, we compare the performance of the SVSSI T 2 chart with the other T 2 control schemes.